Efficient congestion minimisation by successive load shifting in multilayer wireless networks. (May 2018) - Haque, Md. Emdadul; Tariq, Faisal; Dooley, Laurence; Allen, Ben; Sun, Yan
Abstract: Congestion in wireless networks is one of the major causes of system inefficiency, and with router load being the main contributor to overall network traffic flow, congestion is very dependent on the level of router load and how it can be effectively managed. This paper presents a novel low-complexity successive load shifting (SLS) technique for intelligently shifting router load between network routers by predicting the probability of congestion occurrences in the network and exploiting the topology to reassign load to minimise congestion. Crucially, SLS does not compromise the data rate in avoiding congestion and is able to be seamlessly embedded into existing protocols with only a small increase incurred in system overheads. The performance of SLS has been extensively tested and critically evaluated using the widely adopted TCP and UDP protocols, with results confirming both significant throughput gains and superior packet loss performance.